SINGLE AND MIXED BLOOD PROTOZOA INFECTION WITH ANAPLASMA AND THEILERIA IN BUFFALOES (BUBALUS BUBALIS ) IN BAGHDAD - IRAQ - Hasso, Saleem A.; AL - Nashy, Nisreen A. (The Iraqi Journal of Veterinary Medicine, 2021)
One hundred & six blood smears from buffaloes, slaughtered at Al- Futhaliya slaughter house in Baghdad, were examined. Ages of buffaloes ranged from 6 months to 10 years. Numbers of positive blood smears were 48 (45.28%), of them only one showed clinical signs. Single, double, and triple protozoal infections with Anaplasma centrali , Anaplasma marginale, and Theileria annulata, were found. The most common type of infection was the Anaplasma marginale (22.64%), while Anaplasma centrali and Anaplasma centrali + Theileria annulata (0.94%) each. This investigation confirmed the presence of Anaplasma centrali infection in buffaloes for the first time.